The Sustainable Architectural Values of Eclectic Style Shophouses Case Study: Sun Yat Sen Museum Penang, Malaysia - Zwain, Akram; Bahauddin, Azizi (Institut Seni Budaya Indonesia (ISBI) Bandung, 2017)
The Sun Yat Sen shophouse in Penang is a small private Museum, which was converted from a shophouse or townhouse situated in the Armenian Street heritage area of George Town. The building is an example of embraces of the architectural heritage of George Town which is an extra ordinarily beautiful example of Straits Se! lements merchant’s shophouse. Historically, it is associated with the global historical personality of Dr. Sun Yat Sen and his revolutionary movement. This city was added to the UNESCO’s world heritage list in 2008 to acknowledge its rich cultural heritage that constitutes of unique architectural and cultural townscape along the Straits of Melaka. This paper investigates the architectural plan of a shophouse and the values of cultural heritage buildings, which eventually were converted into a Museum in George Town, Penang. Classifi ed as an eclectic style shophouse, it is rich in design and art components featured in its architecture that are still sustaining until today. This building has an interesting mixture of architectural and cultural inspirations adapted from the Chinese origin, with the local Malay ethnicity and the European infl uences that colonised the region. The introduction of new non related architectural components into the southern Chinese style in shophouses in George Town has resulted in the disappearance of this unique style of architecture. This investigation employs a qualitative research approach by documenting evidence and understanding the architectural as well as cultural infl uences of the southern Chinese eclectic style by studying the Sun Yat Sen Museum as a case study. The fi ndings of the research point towards an understanding of the architectural and cultural infl uences that govern the design of the shophouse and its architectural character.